Masas forestales en cinco parques de Neiva: Especies, volumen de madera en pie, análisis estructural y estado fitosanitario (2008)
This research, which emphasizes on the importance of deeply understanding forest masses in urban parks to be able to take advantage of its vegetation, was developed in five parks in Neiva, by means of using a registry card for trees and bushes designed by the author. Hence, the article offers some basic concepts on the topic and presents the particular results obtained for the "Love and Friendship Park", as well as consolidated data for the other four parks chosen for examination.